Ultrasonic vibration-assisted pelleting for cellulosic biofuel manufacturing: investigation on power consumption - Zhang, Qi; Zhang, Pengfei; Pei, Zhijian J.; Wang, Donghai (My University, 2013)
Cellulosic ethanol produced from cellulosic biomass is an alternative to petroleum-based transportation fuels. Raw cellulosic biomass has low density, causing high costs in their storage, transportation, and handling. Ultrasonic vibration-assisted (UV-A) pelleting can increase the density of cellulosic biomass. Effects of UV-A pelleting variables on pellet quality (density, durability, stability, and strength) and sugar yield have been reported. However, power consumption in UV-A pelleting has not been fully investigated. This paper presents an experimental investigation on power consumption in UV-A pelleting of wheat straw. Effects of input variables (biomass moisture content, biomass particle size, pelleting pressure, and ultrasonic power) on power consumption are investigated. Results show that power consumption in UV-A pelleting increases as moisture content and particle size decrease, and as pelleting pressure and ultrasonic power increase.
Keywords: Biofuel; Biomass; Pelleting; Power consumption; Ultrasonic